2022
DOI: 10.1371/journal.pone.0270968
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria and helminth infections in rural communities in northern Sierra Leone, a baseline study to inform Ebola vaccine study protocols

Abstract: Introduction Recurrent parasitic infections may influence the immune response to vaccines. In the Partnership for Research on Ebola VACcinations extended follow-UP and clinical research capacity build-UP (PREVAC-UP) study being undertaken in Mambolo, northern Sierra Leone, participants are being followed up to assess the potential impact of exposure to malaria and/or helminth infections on long-term immune response to two Ebola vaccines. To support the development of the assays that will be used in this evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…This means that vaccination against EVD will be implemented most frequently in areas with a high malaria prevalence. Since malaria is recognized as having an effect on the immune responses of some vaccines [ 13 , 14 , 15 ], we conducted a study to assess whether malaria impaired the immunogenicity of the two-dose Ad26.ZEBOV, MVA-BN-Filo Ebola vaccine regimen in adults and children from Kambia district in Sierra Leone, an area where malaria is highly prevalent [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that vaccination against EVD will be implemented most frequently in areas with a high malaria prevalence. Since malaria is recognized as having an effect on the immune responses of some vaccines [ 13 , 14 , 15 ], we conducted a study to assess whether malaria impaired the immunogenicity of the two-dose Ad26.ZEBOV, MVA-BN-Filo Ebola vaccine regimen in adults and children from Kambia district in Sierra Leone, an area where malaria is highly prevalent [ 18 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EBOVAC-Salone trial occurred between September 2015 and July 2018 in Kambia District, an area in the North of Sierra Leone affected by intense malaria transmission [ 21 ]. Information on the design of the clinical trial can be found on the trial registration page in ClinicalTrials.gov (NCT02509494) and has been described previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The observed lower level in induced immune responses in African countries compared to Europe could be explained by several factors such as human genetic, environmental, or demographic factors. One possible explanation is that recurrent exposure to the parasitic infections that are prevalent in African countries could explain such a decrease [14]. Indeed, studies in both human and animal models have shown that trematode, nematode, and Plasmodium infections can lead to decreased efficacy of previous vaccination and an inability to ward off new infection [15][16][17][18].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Prevalence varies substantially from one country to another and also within country. STH prevalence in Africa ranges between 5% to 20% and Schistosomiasis varies between 10% to 60% [14,[27][28][29][30][31][32][33].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Prevalence varies substantially from one country to another and also within country. STH prevalence in Africa ranges between 5% to 20% and Schistosomiasis varies between 10% to 60% [14,[27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%